The networked instructor: The quality of networks in different stages of professional development. (October 2016) - Van Waes, Sara; Moolenaar, Nienke M.; Daly, Alan J.; Heldens, Henderijn H.P.F.; Donche, Vincent; Van Petegem, Peter; Van den Bossche, Piet
Abstract: This article focuses on the quality of instructional networks in different stages of professional development. Drawing theoretically from social capital theory and literature on teacher interaction, we conducted in-depth interviews with 30 instructors at the university level. Using qualitative social network analysis to capture and analyze networks, we found that the quality of instructors' interactions varied across developmental stages (novice, experienced non-expert, and expert instructors), both in terms of interdependence and opportunities for value creation. These findings offer valuable leverage for shaping educators' everyday professional development and increasing teaching capacity through quality interaction. Highlights: The interdependence in instructors' teaching networks varied but tended to be low. Instructors attributed different types of value to their teaching networks. Instructors in varying developmental stages differed in network quality. In-depth interviews and social network methods were combined. A network mapping tool was used to visualize teaching networks.